2016
DOI: 10.1111/iep.12168
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of naringenin against permethrin‐induced testicular toxicity in rats

Abstract: SUMMARYPermethrin (PM), a synthetic pyrethroid insecticide, has broad toxicity spectra. We aimed to investigate the effects of PM on the testes of adult albino rats, examine the recovery response and evaluate the efficacy of naringenin (NG) supplementation. Adult male albino rats were randomly assigned to five groups of six each: control, NG (50 mg/kg), PM (70 mg/kg), recovery (after subsequent withdrawal of PM) and NG-PM group. All treatments were given by oral gavage for 6 weeks and another 3 weeks for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 84 publications
(130 reference statements)
5
14
0
Order By: Relevance
“…It is demonstrated that in stressful conditions, naringenin has the ability to chelate irons and decrease ROS production. Interestingly, it is related to the fact that naringenin has 5-hydroxy and 4-carbonyl groups in the C-ring which plays a role in ROS scavenging, Cu, and Fe ions interaction [38, 39]. Therefore, adding naringenin to the cryopreservation medium can decrease the stress caused by freezing, consequently can increase motility which was observed in our study.…”
Section: Discussionsupporting
confidence: 55%
“…It is demonstrated that in stressful conditions, naringenin has the ability to chelate irons and decrease ROS production. Interestingly, it is related to the fact that naringenin has 5-hydroxy and 4-carbonyl groups in the C-ring which plays a role in ROS scavenging, Cu, and Fe ions interaction [38, 39]. Therefore, adding naringenin to the cryopreservation medium can decrease the stress caused by freezing, consequently can increase motility which was observed in our study.…”
Section: Discussionsupporting
confidence: 55%
“…This was further seen in the combination treatment, where the sperm counts were decreased compared to the control but higher in comparison to HAART only and Naringenin only treatments. Under stress condition, Naringenin has the potential to chelate irons and scavenge ROS (Mostafa et al ., ). 5‐hydroxy and 4‐carbonyl groups in the C‐ring of Naringenin play a role in ROS scavenging, Cu, and Fe ions interaction.…”
Section: Discussionmentioning
confidence: 97%
“…5‐hydroxy and 4‐carbonyl groups in the C‐ring of Naringenin play a role in ROS scavenging, Cu, and Fe ions interaction. Naringenin also restores mitochondrial membrane potential mitigating mitochondrial dysfunction and subsequent apoptotic cascade (Mostafa et al ., ). This could possibly explain the higher sperm count seen in HAART combined with Naringenin groups compared to HAART, and Naringenin treated groups as Naringenin mitigated the mitochondrial dysfunction and stress induced by HAART exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Among antioxidant components used for male reproductive systems, there is an evidence that naringenin, a well‐known flavonoid, has a considerable influence on the health of testicular cells and can act as a radical scavenger, an immunity system modulator, and an anti‐inflammatory factor . Roy et al demonstrated that narigenin can modulate the levels of ROS and improves diabetes‐induced testicular dysfunction in diabetic rats .…”
Section: Discussionmentioning
confidence: 99%